Peran Komunikasi Internal dalam Corporate Communication untuk Meningkatkan Employee Engagement - Ersa Rahmanda; Flarines Yena Feranza; Nofalia Juliana Sari; Sekar Tijani Putri; 5Riska Ferdiana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This study examines the important role of internal communication in enhancing employee engagement within the context of corporate communication. Effective internal communication is crucial for fostering a positive organizational culture, ensuring smooth operations, and building trust between management and employees. Using the Two-Way Symmetrical Model by Grunig and Hunt, this paper emphasizes the importance of reciprocal communication in creating open, transparent, and inclusive communication channels that encourage engagement and collaboration. The study employs a qualitative approach with a descriptive method, relying on literature analysis. The findings indicate that organizations face significant challenges in managing communication across generations in the workforce. Differences in communication preferences, generational values, and technological barriers are factors that impact the effectiveness of internal communication. To address these challenges, appropriate communication strategies need to be implemented. This study proposes several strategies, such as multichannel communication, digital literacy training, message customization, and participative leadership. These strategies can enhance employee engagement, strengthen internal communication, and contribute to the long-term success of the organization.